PENGARUH TINGKAT PEMBIAYAAN MUDHARABAH TERHADAP TINGKAT RASIO PROFITABILITAS PADA KOPERASI JASA KEUANGAN SYARIAH (KJKS) MANFAAT SURABAYA - Imam Buchori; Aji Prasetyo (El-Qist: Journal of Islamic Economics and Business (JIEB), 2014)
Many financial institutions those were born with the Shariah-based in Indonesia--including non-bank financial institutions, among them are Islamic insurance, Shariah pawnshop, Shariah financial services cooperatives, and more. Shariah-compliant financial services cooperatives (KJKS) Manfaat Surabaya is still classified as "new" in Indonesia, in which retained the principle of kinship as a guide of the cooperative itself. Various systems were much changed, from conventional systems to the Islamic system, especially in terms of contract and financial accounting standards. Then came the question, whether the views of society and the level of public confidence as well as different? Of course a lot of things to be able to prove from the above questions, one of which is the level of profitability, as well as a large number of levels KJKS Groove financing given to the community. The greater the level of profitability means the level of public confidence about the existence of KJKS in Indonesia also getting bigger. Many financing products of KJKS Manfaat are given to the public, one of which is the mudharabah financing which is very influential on the profit orientation of each financial institution of Sharia. This research is the kind of quantitative research with data analysis using simple regression and t tests to find out the significance of the influence of mudharabah financing against a ratio of profitability in KJKS Manfaat Surabaya.